2021
DOI: 10.1016/j.jaerosci.2020.105626
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the transport, hygroscopic growth, and deposition of multi-component droplets in a simplified airway with realistic thermal boundary conditions

Abstract: Accurate predictions of the droplet transport, evolution, and deposition in human airways are critical for the quantitative analysis of the health risks due to the exposure to the airborne pollutant or virus transmission. The droplet/particle-vapor interaction, i.e., the evaporation or condensation of the multi-component droplet/particle, is one of the key mechanisms that need to be precisely modeled. Using a validated computational model, the transport, evaporation, hygroscopic growth, and deposition of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 48 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…The geometric size is illustrated in previous studies. [19][20][21] proposed an empirical correlation for particle deposition in the MT region based on previous human experimental results. 22 Later, Zhang developed the MT model used in this study and evaluated its performance of mimicking particle deposition.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The geometric size is illustrated in previous studies. [19][20][21] proposed an empirical correlation for particle deposition in the MT region based on previous human experimental results. 22 Later, Zhang developed the MT model used in this study and evaluated its performance of mimicking particle deposition.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Besides models for simulation, Chen et al 249 reported a prediction model of hygroscopic droplet deposition in airways using parameters such as temperature distribution, relative humidity distribution, deposition efficiencies, droplet or particle distribution, and droplet growth ration distributions (Figure 4c). It is found that high inhalation flow rate can decrease the mucus temperature and airway relative humidity and cause the growth of hydroscopic droplets.…”
Section: Particle Transport Through Mclsmentioning
confidence: 99%
“…(c) Illustration of diameters and locations for the deposited droplets and escaped droplets and particles when the flow rate is 15 L/min with the same initial Stk = 0.036. Panel (c) reproduced with permission from ref . Copyright 2021 Elsevier.…”
Section: Particle Transport Through Mclsmentioning
confidence: 99%
“…The Lagrange method adds a random velocity component to the velocity term of the equation of motion. In a rotating coordinate system, the equation of motion of particles derived by Basset, Boussinesq and Oseen is shown in equation (Chen, et al, 2021;Ding, et al, 2021;Wittmann, et al, 2021) Eq. 5. where m p is the particle quality, u is the velocity, ρ is the density, µ is the fluid kinematic viscosity coefficient, C D is the drag coefficient, F b is the buoyancy due to gravity, ω is the rotational angular velocity, R is the calibrate the direction vector of the rotation axis, F U is the user-defined other forces, f, p represents vapor phase and liquid respectively, t 0 is the start time, t 1 is the end time.…”
Section: Droplet Transport Modelmentioning
confidence: 99%